A novel approach for manual de-torsion of an atypical (outward) testicular torsion with bedside Doppler ultrasonography guidance - Güneş, Mustafa; Umul, Mehmet; Çelik, Ahmet Orhan; Armağan, Hamit Hakan; Değirmenci, Bumin (Canadian Urological Association Journal, 2015)
A 17-year-old boy presented with right testicular torsion to the lateral side. Torsion was diagnosed by physical examination; the colour Doppler ultrasonography (CDU) confirmed right testicular torsion with minimal peripheral hydrocele. Transverse and longitudinal examination of the spermatic cord with ultrasound and CDU revealed a counter-clockwise testicular torsion. Manual de-torsion was performed in a clockwise direction (720o) and testicular blood flow and the neutral position of the spermatic cord were confirmed by CDU. We did not encounter a residual twist of the spermatic cord upon surgical exploration. In our experience, ultrasound and CDU may predict the direction of testicular torsion and may allow appropriate management of cases prior to surgery.